Role of endotracheal tube size on nasal and laryngeal morbidity during awake fiberoptic nasotracheal intubation: A Randomized controlled trial - Stalin Vinayagam; Thirumurugan Arikrishnan; Pankaj Kundra; Sunil Kumar Saxena (Wolters Kluwer Medknow Publications, 2022)
Background and Aims: Awake fibreoptic nasotracheal intubation is associated with adverse airway and hemodynamic complications. The aim of this study was to evaluate the role of endotracheal tube size on nasal and laryngeal morbidity during awake fibreoptic-guided nasotracheal intubation. Material and Methods: Eighty patients recruited to undergo awake fibreoptic intubation were randomly allocated to Group C (standard size endotracheal tube) and Group S (small size endotracheal tube followed by exchange to standard size using Airway Exchange Catheter under general anesthesia). Nasal morbidity was assessed by incidence of epistaxis, olfactory acuity, and mucociliary clearance. Patient discomfort during intubation was assessed using grimace score and hemodynamic parameters were recorded. Postoperatively, the incidence of nasal and laryngeal injury was recorded using nasendoscopy and telelaryngoscopy, respectively. Results: Demographic profile between the two groups was comparable. Epistaxis was noted in 47.5% of patients in group C as compared to 12.5% in group S. Postoperative olfactory acuity was decreased [2 (1-4) vs 4 (2-5)] and saccharin clearance time was prolonged (314 s vs 134 s) in Group C as compared to Group S. (P-value <0.001) Higher grimace score [2 (1-3) vs 1 (0-2)] and increased hemodynamic response was demonstrated in Group C. (P-value <0.001) Incidence of nasal injury [2 (1-4) vs 1 (0-2)] and laryngeal injury [1 (0-2) vs 0 (0-2)] was more in Group C as compared to Group S. Conclusion: Awake fibreoptic nasotracheal intubation with small size endotracheal tube followed by exchange to standard size under general anesthesia reduces nasal, laryngeal, and hemodynamic complications.